2022
DOI: 10.3389/fmars.2022.834337
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Regulates Bacterial Processes That Play a Major Role in Marine Biogeochemical Cycles

Abstract: Bacteria play a crucial role in marine biogeochemistry by releasing, consuming and transforming organic matter. Far from being isolated entities, bacteria are involved in numerous cell–cell interactions. Among such interactions, quorum sensing (QS) allows bacteria to operate in unison, synchronizing their actions through chemical communication. This review aims to explore and synthesize our current knowledge of the involvement of QS in the regulation of bacterial processes that ultimately impact marine biogeoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 281 publications
(446 reference statements)
0
11
0
Order By: Relevance
“…Actinobacteria are widespread in marine environments and reached high abundance in deep-sea sediments, organic aggregates and macroalgae [ 54 ]. In terms of QS, several bacteria belonging to Actinobacteria , which were isolated from marine snow [ 3 ] and microbial mats in Shark Bay Australia [ 16 ] or reef macroalgae [ 55 ], have been identified to show AHL-producing activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actinobacteria are widespread in marine environments and reached high abundance in deep-sea sediments, organic aggregates and macroalgae [ 54 ]. In terms of QS, several bacteria belonging to Actinobacteria , which were isolated from marine snow [ 3 ] and microbial mats in Shark Bay Australia [ 16 ] or reef macroalgae [ 55 ], have been identified to show AHL-producing activities.…”
Section: Discussionmentioning
confidence: 99%
“…The QS pathways presented among marine bacteria may directly or indirectly influence biogeochemical cycles through the regulation of genes and EE activities, and the degradation of marine particles and marine snows [ 54 ]. Hmelo et al [ 46 ] demonstrated that the addition of 3OC 6 -HSL or 3OC 8 -HSL improved the extracellular aminopeptidase and phosphatase activities of bacterial communities colonizing marine snow.…”
Section: Discussionmentioning
confidence: 99%
“…To further advance our knowledge, additional studies are necessary to experimentally validate the complete mechanism. Techniques using biosensor reporter strains [78,79] and analytical methods like liquid chromatography and mass spectrometry [18,80]…”
Section: Discussionmentioning
confidence: 99%
“…Detecting QS/QQ systems in environmental samples can be challenging due to the diversity of gene sequences encoding these systems [18]. Advanced approaches, such as combining comprehensive environmental databases and large-scale metagenomics data, can increase our ability to identify organisms that have the potential to perform QS/QQ functions [17,18]. Ammonia-oxidizing archaea (AOA) are among the most abundant planktonic archaea in the ocean [19].…”
Section: Introductionmentioning
confidence: 99%
“…QS regulation of pathways for organic matter degradation, nutrient acquisition, colonization processes and microbial interactions has been studied extensively in marine bacteria ( Urvoy et al, 2022 ). Previous studies have also discussed the influence of QS in regulating production, release and/or uptake of specific metabolites ( An et al, 2014 ; Johnson et al, 2016 ; Landa et al, 2017 ; McRose et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%